2007
DOI: 10.1590/s1806-37132007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Características clínico-demográficas de pacientes hospitalizados com tuberculose no Brasil, no período de 1994 a 2004

Abstract: Objective: To describe the demographic and clinical characteristics of patients with tuberculosis hospitalized in the Nestor Goulart Reis Hospital, located in the city of Américo Brasiliense, Brazil. Methods: Epidemiological investigation by means of an observational, retrospective, descriptive study based on the medical charts of patients diagnosed with tuberculosis and hospitalized between 1994 and 2004. Results: There were 1787 patients diagnosed with tuberculosis during the period evaluated. Of those, 117 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
1
6
0
17
Order By: Relevance
“…Among the social factors related to TB-HIV co-infected cases, we highlight the association for hospitalization related to alcohol use and dependence, confirming other studies that showed strong association between TB and alcoholism, which is understandable because cachexia due to alcoholism predisposes individuals to low immunity (15) , increased by the establishment of co-infection, leading to hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…Among the social factors related to TB-HIV co-infected cases, we highlight the association for hospitalization related to alcohol use and dependence, confirming other studies that showed strong association between TB and alcoholism, which is understandable because cachexia due to alcoholism predisposes individuals to low immunity (15) , increased by the establishment of co-infection, leading to hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…O estudo de Campani et al 9 , em Porto Alegre, demonstrou resultados semelhantes: quase 75,9% dos casos tinham 7 anos ou menos de estudo. No estudo de Natal et al 23 (89,7%) e de Severo et al 24 , em São Paulo, o resultado foi de 77,8%.…”
Section: Aspectos éTicosunclassified
“…Quanto à escolaridade, os dois grupos se concentraram principalmente no nível de Ensino Fundamental, o que revela o baixo nível de escolaridade dos pacientes estudados, confirmando a tendência secular da doença, cuja incidência é maior em populações mais desfavorecidas (11) . A distribuição dos pacientes nos dois grupos investigados na presente pesquisa, com relação à faixa etária, esteve entre 16 e 59 anos, estando de acordo com outros estudos (11,12) e se assemelhando com a realidade brasileira, em que a TB atinge principalmente a população economicamente ativa (11) , conferindo significado social à doença.…”
Section: Discussionunclassified